1997
DOI: 10.1117/12.273711
|View full text |Cite
|
Sign up to set email alerts
|

<title>Data analysis results from the GOLD experiments</title>

Abstract: Analyses of uplink and downlink data from recent free-space optical communications experiments carried out between Table Mountain Facility (near Pasadena, CA) and the Japanese ETS-VI satellite are presented. Fluctuations in signal power collected by the satellite's laser communication experiment (LCE) due to atmospheric scintillation and its amelioration using multiple uplink beams are analyzed and compared to experimental data. Downlink data was analyzed to determine the cause of a larger than expected variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…GOLD demonstration in 1998 showed that the scintillation index was drastically improved with four 514.5 nm multiple beams for uplink transmission. It was reported that the value of scintillation was 0.12 with two beams, however, its value reduces to 0.045 with four beams [227]. Reduction in the intensity variance by a factor of square root of the number of transmitting antennae is observed in [228], [229] for ground-to-satellite FSO uplink.…”
Section: Mitigation Techniquesmentioning
confidence: 99%
“…GOLD demonstration in 1998 showed that the scintillation index was drastically improved with four 514.5 nm multiple beams for uplink transmission. It was reported that the value of scintillation was 0.12 with two beams, however, its value reduces to 0.045 with four beams [227]. Reduction in the intensity variance by a factor of square root of the number of transmitting antennae is observed in [228], [229] for ground-to-satellite FSO uplink.…”
Section: Mitigation Techniquesmentioning
confidence: 99%
“…In our simulation, we assumed the following; (1) the phase of the propagating light wave is modulated in a thin turbulent layer; (2) there is no effect on the light wave between the turbulent layer. The light wave propagation is calculated based on both geometrical optics and the scalar wave theory using.…”
Section: Simulation Of the Ao Systemmentioning
confidence: 99%
“…Prior experience 6,7,8 has shown that these effects are particularly severe for a single laser beam and can be mitigated by using multiple, mutually incoherent, co-propagating beams. Likewise, this strategy will be implemented by the OCTL uplink laser assembly.…”
Section: Introductionmentioning
confidence: 98%